Determination of Residents’ Perception on Health and Residential Value from Telecommunication Tower - Norazmawati Md. Sani; Ahmad Fahmi Lim Bin Abdullah; Kai Xin Tay (Modern Perspectives in Economics, Business and Management Vol. 5, 2021)
In last decades, due to the cellular phone systems and the rapid increase in the number of users of cellular phones, a growing concern about the possible health hazards has increased among public and scientists, particularly exposure to Electromagnetic Field (EMFs). The objectives of this research are to determine the residents’ perceptions on the health impacts of telecommunication base stations in Malaysia and to examine its impacts on property value. Data from a face-to-face survey conducted in all states of Malaysia (N=509). The respondents were required to complete a standardized questionnaire that focused on the relevant psychological and psychobiological reactions measurement. Stata Software was used for statistical analysis using the Chi-square test with Fisher’s exact and binomial logistic regression. The result shows that only one health symptom headache was statistically significant for both residents who live near to base station (<300m) and those living far from base station (>300m). The findings reveal that appearance of telecommunication tower is not influence the property price except one health symptom fatigue. The recommendations are also outlined in this paper.